The results of deep magnetotelluric sounding for studying the Nha Trang - Tanh Linh fault - Son, Vo Thanh; Minh, Le Huy; Phuong, Nguyen Hong; Marquis, Guy; Thanh, Nguyen Ha; Nam, Vu Dao; Vinh, Nguyen Ba; Quyen, Dao Van; Thang, Nguyen Chien; Viet, Nguyen Hong (Vietnam Journal of Marine Science and Technology, 2017)
The profile of deep magnetotelluric sounding (MT) from Duc Trong - Tuy Phong has been carried out in Lam Dong and Binh Thuan provinces. The length of the Duc Trong - Tuy Phong profile is about 80 km with 15 stations and the distance between the stations measures about 5 km. Two-dimensional MT inversion was used to find a resistivity model that fits the data. The 2D resistivity model allows determining position and development formation of the Nha Trang - Tanh Linh fault. This is the deep fault, which is showed by the boundaries of remarkable change of resistivity. In the near surface of the Earth (from ground to the depth of 6 km), the angle of inclination of this fault is about 60o; in the next part, the direction of the Nha Trang - Tanh Linh faut is vertical. Geoelectrical section of the Nha Trang - Tanh Linh profile shows that the resistivity of mid-crust is higher than that of lower-crust and of upper-crust.